AMERICAN POLICY TOWARD CENTRAL ASIA AND UZBEKISTAN’S GEOPOLITICAL SIGNIFICANCE (1991–2024) - Xatamov Tursunboy Xamdam o'g'li (The Conference Hub, 2025)
From 1991 to 2024, U.S. policy toward Central Asia was primarily oriented toward strengthening security, stability, and democratic institutions. Following the war in Afghanistan, Washington significantly intensified its engagement in the region. However, persistent tensions over human rights issues repeatedly constrained the depth and scope of cooperation. In the 2010s, the United States sought to promote regional integration through the C5+1 diplomatic format. Throughout this period, Uzbekistan pursued a “multi-vector” foreign policy aimed at maintaining balanced relations with major powers. After 2016, U.S.–Uzbekistan relations gained considerable momentum, particularly in the economic and security domains. At the same time, human rights concerns remained a salient and unresolved issue. In the 2020s, the growing influence of Russia and China compelled Tashkent to recalibrate its strategic orientations. The year 2024 marked a notable turning point in energy security following the conclusion of nuclear energy agreements with Russia. In conclusion, although U.S. policy has consistently emphasized regional integration and stability, Uzbekistan—through its multi-vector approach—has emerged as an increasingly active and autonomous player in Central Asia’s geopolitical landscape.
Keywords: U.S. policy, Central Asia, Uzbekistan, geopolitics, security, multi-vector policy, integration, stability, cooperation, development, human rights, democracy, foreign policy, diplomacy, independence, Russia, China, energy, nuclear, economy, strategy, region, balance, initiatives, global processes,